Advanced Laser Technology for Quantum Communications (Tutorial Review). Issue 10 (22nd August 2021) - Paraïso, Taofiq K.; Woodward, Robert I.; Marangon, Davide G.; Lovic, Victor; Yuan, Zhiliang; Shields, Andrew J.
Abstract: Quantum communications is the art of exchanging and manipulating information beyond the capabilities of the conventional technologies using the laws of quantum mechanics. With applications ranging from quantum computing to cryptographic systems with information‐theoretic security, there is strong incentive to introduce quantum communications into many areas of the society. However, an important challenge is to develop viable technologies meeting the stringent requirements of low noise and high coherence for quantum state encoding, of high bit rate and low power for the integration with classical communication networks, and of scalable and low‐cost production for a practical wide‐deployment. This tutorial presents recent advances in laser modulation technologies that have enabled the development of efficient and versatile light sources for quantum communications, with a particular focus on quantum key distribution (QKD). Such approaches have been successfully used to demonstrate several QKD protocols with state‐of‐the‐art performance. The applications and experimental results are reviewed and interpreted in the light of a complete theoretical background, allowing the reader to model and simulate such sources. Abstract : The scalability and efficiency of quantum communication hardware constitute the most important challenge for a practical and viable deployment of the technology. Advanced modulation techniques exploiting the versatility of semiconductor lasers directly address this challenge and are successfully applied to demonstrate high‐performance quantum cryptography protocols. These concepts are reviewed in a complete and unified theoretical framework supported by state‐of‐the‐art experimental achievements.